2002
DOI: 10.1002/qua.10362
|View full text |Cite
|
Sign up to set email alerts
|

Substituent effects on the electronic structure and pKa of benzoic acid

Abstract: ABSTRACT:The effects of substituents on the pK a s of a set of 16 substituted benzoic acids have been examined using density functional theory [B3LYP/6-311G(d, p)] calculations. A variety of quantum chemical parameters were examined as indicators for the variations observed in the experimental pK a s, including the Löwdin, Mulliken, AIM, and natural population analysis charges (Q L , Q M , Q A , and Q n ) on atoms of the dissociating carboxylic acid group, the energy difference (⌬E prot ) between the carboxyli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
133
1
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(144 citation statements)
references
References 17 publications
8
133
1
2
Order By: Relevance
“…Charges on the ionized oxygen (O -) and the charge on the whole corresponding conjugate anion, (AsO(OH)O -), were also determined and are shown in Table 3. 21,[57][58] Good correlation between calculated pKa and the APT charges can be observed. Table 3.…”
Section: Atomic Chargesmentioning
confidence: 75%
“…Charges on the ionized oxygen (O -) and the charge on the whole corresponding conjugate anion, (AsO(OH)O -), were also determined and are shown in Table 3. 21,[57][58] Good correlation between calculated pKa and the APT charges can be observed. Table 3.…”
Section: Atomic Chargesmentioning
confidence: 75%
“…[29] However, a recent study showed that natural population analysis (NPA) charges on carboxylate groups had the strongest correlation with the corresponding pK a values in a series of para-functionalised aromatic carboxylic acids. [33] To gain more insight into the influence of the substituent on the properties of the metal centre, several para-substituted NCN-pincer platinum(ii) chloride complexes [PtCl(NCN-Z)] were investigated by the DFT method B3LYP/LANL2DZ [34] and natural bond order population analysis as implemented in Gaussian 98. [35] Of specific interest in our calculations was the influence of the para substituent on the calculated charges of the platinum centres and the calculated structural features in comparison with single-crystal X-ray structures.…”
mentioning
confidence: 99%
“…The calculated energy variables were theoretically calculated using the three methods, and at the five thermal degrees of all imines, which represent the stability of molecules through interference and spatial changes (HOMO, LUMO, hardness, chemical electron voltage, and electrolyte guide). In the literature (Chipman, 2002;Ebead et al, 2010) (Hollingeworth et al, 2002). These variables represent the center of the interaction for the ionization constants.…”
Section: Resultsmentioning
confidence: 99%